2014
DOI: 10.1007/s00262-014-1593-0
|View full text |Cite
|
Sign up to set email alerts
|

Harmonisation of short-term in vitro culture for the expansion of antigen-specific CD8+ T cells with detection by ELISPOT and HLA-multimer staining

Abstract: Ex vivo ELISPOT and multimer staining are well-established tests for the assessment of antigen-specific T cells. Many laboratories are now using a period of in vitro stimulation (IVS) to enhance detection. Here, we report the findings of a multi-centre panel organised by the Association for Cancer Immunotherapy Immunoguiding Program to investigate the impact of IVS protocols on the detection of antigen-specific T cells of varying ex vivo frequency. Five centres performed ELISPOT and multimer staining on centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…Importantly, our observed results fit into recently published observations addressing the benefits and outcomes of extended resting of thawed PBMC on their functionality [ 13 , 18 , 32 ], as demonstrated with different experimental approaches. ELISPOT is one of the most commonly used tests in the immune monitoring setting.…”
Section: Resultssupporting
confidence: 89%
“…Importantly, our observed results fit into recently published observations addressing the benefits and outcomes of extended resting of thawed PBMC on their functionality [ 13 , 18 , 32 ], as demonstrated with different experimental approaches. ELISPOT is one of the most commonly used tests in the immune monitoring setting.…”
Section: Resultssupporting
confidence: 89%
“…We observed that the clone of anti-CD124 antibody and the composition of the lineage cocktail significantly influenced the quantification of CD124 + MDSCs and immature MDSCs, respectively. The issue of the heterogeneity of reagents was also present in previous proficiency panels, in which a partial standardization of reagents had been suggested [ 25 ], especially for culturing of PBMCs intended to be used for functional T cell assays [ 23 , 26 , 27 ]. The MDSC proficiency panel introduced the use of a DCM, and, as expected, we observed that the percentages of several MDSC subsets, and in particular of granulocytic ones, were significantly reduced by dead-cell exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, evaluation of the cellular immune responses is necessary to compare the ability of the 2 different immunostimulatory sequences to induce the activation of T-helper cells, as measured by the production of IFN-g and capture using ELISPOT assay. 42 …”
Section: Discussionmentioning
confidence: 99%